Reproductive Biology of Triatoma brasiliensis (Hemiptera, Triatominae) during the Imaginal Molt - Alevi, Kaio Cesar Chaboli (Am J Trop Med Hyg, 2016)
The triatomines are vectors of the protozoan Trypanosoma cruzi, etiologic agent of Chagas disease. These insects are sexually active after the imaginal molt. Some aspects have been studied in Triatoma brasiliensis during the imaginal molt, such as autogeny in virgin females and the relationship between blood ingestion by fifth instar nymph and the realization of the imaginal molt. Thus, to aid in the understanding of reproductive biology and developmental physiology of these vectors, this article analyzes the spermatogenesis of T. brasiliensis during the imaginal molt. The analysis of the seminiferous tubules from males in the fifth instar during imaginal molt has demonstrated that T. brasiliensis has only a few spermatids and a plentiful quantity of sperm. Thus, we suggest that during imaginal molt the cell division is disrupted aiming to reduce energy costs and the differentiation into sperm is stimulated to ensure the paternity of the adult male.